Uji Aktivitas Antioksidan Ekstrak Etanol Lissoclinum patella Yang Diperoleh Dari Pantai Parentek Kabupaten Minahasa - Adithya Yudistira; Yuanita Amalia Hariyanto; Pricillia Esterlita Mintadoa (PHARMACON, 2024)
Tunicates are one of the marine organisms that have the potential to produce secondary metabolite compounds that have many benefits. One of the functions of secondary metabolites is as antioxidants. Antioxidants are compounds that can inhibit the oxidation process caused by free radicals. This study aims to determine the antioxidant activity of ethanol extract produced by Lissoclinum patella using DPPH (1,1-diphenyl-2-picrylhydrazyl) method obtained from Parentek Beach, Minahasa Regency. This research is a laboratory experiment with maceration method using 95% ethanol solvent. Antioxidant testing using DPPH (1,1-diphenyl-2-picrylhydrazyl) method with 5 series of sample concentrations (20, 40, 60, 80, 100 ppm) measured using UV-Vis spectrophotometer with absorbance value measured at 517 nm wavelength. The results of the study obtained the average percent inhibition value obtained at concentrations of 20, 40, 60, 80, 100 ppm respectively were 48.06%, 56.52%, 62.27%, 63.80%, 68.03%. This study concludes that Lissoclinum patella tunicata extract has antioxidant activity at concentrations of 20, 40, 60, 80, 100 ppm.